(untitled) (Nativa, 2026)
A mudança no uso do solo pode provocar alterações na dinâmica do carbono e nas frações da matéria orgânica, especialmente em camadas mais profundas, variando conforme o bioma. Este estudo teve como objetivo avaliar a influência de diferentes sistemas de uso do solo nos estoques de carbono e nas frações da matéria orgânica nos biomas Caatinga e Cerrado, no estado do Piauí, Brasil. O experimento foi conduzido em áreas sob três usos (vegetação nativa, pastagem e agricultura), com coletas de solo em sete profundidades (0–10, 10–20, 20–30, 30–40, 40–60, 60–80 e 80–100 cm), totalizando 126 unidades amostrais. Foram determinados os teores de matéria orgânica do solo (MOS), carbono orgânico total (COT), estoque de carbono (EC), matéria orgânica particulada (MOP), carbono da MOP (C-MOP) e carbono associado aos minerais (C-CAM). Observou-se que os teores de MOP foram significativamente superiores nas camadas superficiais, com maior acúmulo nas áreas de pastagem no Cerrado. Os estoques de carbono nas áreas de pastagem e de agricultura não diferiram das áreas de vegetação nativa em ambos os biomas, indicando baixa degradação. Contudo, os biomas apresentaram respostas distintas ao uso agrícola, evidenciando a necessidade de manejo específico para manter os estoques de carbono e a qualidade do solo. Palavras-chave: agricultura; pastagem; mata nativa; uso do solo; semiárido. Organic matter and carbon stocks under different land-use systems in the Cerrado and Caatinga biomes of Brazil ABSTRACT: Land-use change can alter carbon dynamics and soil organic matter fractions, especially in deeper soil layers, with variations depending on the biome. This study aimed to evaluate the influence of different land-use systems on carbon stocks and soil organic matter fractions in the Caatinga and Cerrado biomes, located in the state of Piauí, Brazil. The study was conducted in areas under three land-use types (native vegetation, pasture, and agriculture), with soil sampling at seven depths (0–10, 10–20, 20–30, 30–40, 40–60, 60–80, and 80–100 cm), totaling 126 sampling units. The following parameters were analyzed: soil organic matter (SOM), total organic carbon (TOC), carbon stock (CSTOCK), particulate organic matter (POM), particulate organic carbon (C-POM), and mineral-associated organic carbon (MOC). Results showed that POM content was significantly higher in the surface layers, with greater accumulation in pasture areas of the Cerrado biome. Carbon stocks in pasture and the agricultural regions did not differ from those in native vegetation in both biomes, indicating low levels of degradation. However, the biomes responded differently to agrarian use, highlighting the need for biome-specific management strategies to maintain soil carbon stocks and ensure soil quality. Keywords: agriculture; pasture; native vegetation; land use; semiarid.